Caterogrizing the Spectrum of Coordination Technology. - Sarma, Anita; Redmiles, David; Van der Hoek, André (Computer (00189162), 2010)
The article explains the Coordination Pyramid, which may be used to lessen coordination problems and handle paradigm shifts resulting from technological advances or organizational changes. The pyramid covers the coordination paradigms of basic functionality, structured processes, information discover, contextual information and integrated operations across three aspects which are communication, artifact management and task management. The author also provides information on available tools for the three aspects.